Prognostic Significance of Serum Cholinesterase Level in Patients With Acute Decompensated Heart Failure With Preserved Ejection Fraction: Insights From the PURSUIT‐HFpEF Registry. Issue 1 (7th January 2020) - Seo, Masahiro; Yamada, Takahisa; Tamaki, Shunsuke; Hikoso, Shungo; Yasumura, Yoshio; Higuchi, Yoshiharu; Nakagawa, Yusuke; Uematsu, Masaaki; Abe, Haruhiko; Fuji, Hisakazu; Mano, Toshiaki; Nakatani, Daisaku; et al.
Abstract : Background: Malnutrition is one of the most important comorbidities in patients with heart failure with preserved ejection fraction. We recently reported the prognostic significance of serum cholinesterase level and superior predictive power of cholinesterase level to other objective nutritional indices such as the controlling nutritional status score, prognostic nutritional index, and geriatric nutritional risk index in patients with acute decompensated heart failure. The aim of this study was to clarify the prognostic role of cholinesterase in patients with heart failure with preserved ejection fraction/acute decompensated heart failure and investigate incremental cholinesterase value. Methods and Results: We prospectively studied 274 consecutive patients from the PURSUIT‐HFpEF (Prospective Multicenter Observational Study of Patients with Heart Failure With Preserved Ejection Fraction) study. During a follow‐up period of 1.2±0.6 years, 56 patients reached the composite end points (cardiovascular death and readmission for worsening heart failure). In the multivariable Cox analysis, cholinesterase level was significantly associated with the composite end points after adjustment for major confounders. A Kaplan–Meier analysis revealed that patients with low cholinesterase levels (stratified by tertile) had significantly greater risk of reaching the composite end points than those with middle or high cholinesterase levels ( P =0.0025). Cholinesterase level showed the best C‐statistics (0.703) for prediction of the composite end points among the objective nutritional indices. C‐statistics of the Meta‐Analysis Global Group in Chronic Heart Failure (MAGGIC) risk score for prediction of the composite end points were improved when cholinesterase level was added (C‐statistics, from 0.601 to 0.705; P =0.0408). Conclusions: Cholinesterase was a useful prognostic marker for prediction of adverse outcome in patients with heart failure with preserved ejection fraction/acute decompensated heart failure.